MicroRNAs in obesity, sarcopenia, and commonalities for sarcopenic obesity: a systematic review. Issue 1 (4th January 2022) - Dowling, Lisa; Duseja, Ankita; Vilaca, Tatiane; Walsh, Jennifer S.; Goljanek‐Whysall, Katarzyna
Abstract: Sarcopenic obesity is a distinct condition of sarcopenia in the context of obesity, with the cumulative health risks of both phenotypes. Differential expression of microRNAs (miRNAs) has been reported separately in people with obesity and sarcopenia and may play a role in the pathogenesis of sarcopenic obesity. However, this has not been explored to date. This study aimed to identify differentially expressed miRNAs reported in serum, plasma, and skeletal muscle of people with obesity and sarcopenia and whether there are any commonalities between these conditions. We performed a systematic review on Embase and MEDLINE (PROSPERO, CRD42020224486) for differentially expressed miRNAs (fold change >1.5 or P ‐value <0.05) in (i) sarcopenia or frailty and (ii) obesity or metabolic syndrome. The functions and targets of miRNAs commonly changed in both conditions, in the same direction, were searched using PubMed. Following deduplication, 247 obesity and 42 sarcopenia studies were identified for full‐text screening. Screening identified 36 obesity and 6 sarcopenia studies for final inclusion. A total of 351 miRNAs were identified in obesity and 157 in sarcopenia. Fifty‐five miRNAs were identified in both obesity and sarcopenia—by sample type, 48 were found in plasma and one each in serum and skeletal muscle. Twenty‐four miRNAs were identified from 10 of the included studies as commonly changed in the same direction (22 in plasma and one each in serum and skeletal muscle) in obesity and sarcopenia. The majority of miRNA‐validated targets identified in the literature search were members of the phosphoinositide 3‐kinase/protein kinase B and transforming growth factor‐β signalling pathways. The most common targets identified were insulin‐like growth factor 1 (miR‐424‐5p, miR‐483‐3p, and miR‐18b‐5p) and members of the SMAD family (miR‐483‐3p, miR‐92a‐3p, and miR‐424‐5p). The majority of commonly changed miRNAs were involved in protein homeostasis, mitochondrial dynamics, determination of muscle fibre type, insulin resistance, and adipogenesis. Twenty‐four miRNAs were identified as commonly dysregulated in obesity and sarcopenia with functions and targets implicated in the pathogenesis of sarcopenic obesity. Given the adverse health outcomes associated with sarcopenic obesity, understanding the pathogenesis underlying this phenotype has the potential to lead to effective screening, monitoring, or treatment strategies. Further research is now required to confirm whether these miRNAs are differentially expressed in older adults with sarcopenic obesity.